Solitary acrometastasis of the phalanx as initial presentation of an oligometastatic Kirsten rat sarcoma viral oncogene homolog-mutated lung adenocarcinoma: a case report - Pușcașu, Alexandra-Ioana; Moinard-Butot, Fabien; Antoni, Delphine; Schott, Roland; Somme, Laura (Journal of medical case reports, 2023)
Background Acrometastasis is an uncommon finding in non-small cell lung cancer and is usually a sign of multimetastatic disease. Few case reports have suggested solitary digital metastasis as the single secondary lesion of oligometastatic non-small cell lung cancer. Case presentation This case report describes an unusual presentation of a Kirsten rat sarcoma viral oncogene homolog-mutated lung adenocarcinoma with a solitary bone metastasis in the fourth finger medial phalanx, which was also the first sign of the disease, in a 63-year-old Caucasian female patient. Digital surgical amputation was performed. After histopathological confirmation and radiological exclusion of other secondary lesions, chemoimmunotherapy in a first-line setting was initiated. A partial metabolic response in the primary lung lesion was observed after four cycles. Maintenance therapy is currently being continued. Conclusion Solitary digital metastasis is a rare finding in non-small cell lung cancer. Further studies are needed to investigate the mechanisms behind this particular dissemination process.